CONFLICT OF COASTAL SPACE UTILIZATION IN TELENG RIA BEACH WITH A SOCIO-SPATIAL APPROACH - Agus Wahyudi; Wildan Taufik Raharja; Lunariana Lubis; Achmad Zakaria (DIA: Jurnal Administrasi Publik, 2025)
Social conflict in the coastal community of Teleng Ria Beach, Pacitan, East Java, is linked to the use of coastal space for lobster seed fishing (benur). The conflict involves local fishermen, the government, and the private sector, due to the misalignment of lobster seed catching activities with government regulations, which permit catching only for cultivation purposes in Indonesia. However, local fishermen sell the seeds for export to Singapore through collectors. The conflict escalated when PT El-John Tirta Emas banned local fishermen from parking their boats near the tourist area of Teleng Ria Beach, citing disturbances to visitors' comfort. Local fishermen opposed this ban, leading to increased tension between the parties involved. This research aims to identify and analyze the conflict, assess potential resolutions, and evaluate the impact if the conflict persists. A socio-spatial approach is used to understand the relationship between space and people, and how people perceive their environment. The research uses a qualitative case study approach. The results reveal that the conflict over coastal space utilization at Teleng Ria Beach can be viewed from three perspectives: spatial practice (physical space), representations of space (government policy), and space of representation (social space). Conflicts arise from boat parking management, seed-catching policies, and cultural differences and fishery business waste.